DAMPAK PARIWISATA TERHADAP KUALITAS AIR DANAU BERATAN BERDASARKAN PARAMETER BOD DAN COD - Arik Agustina; I Ketut Muliadiasa (JURNAL MANAJEMEN KULINER, 2023)
The purpose of this study was to analyze the impact of tourism on the water quality of Lake Beratan based on BOD and COD parameters. This research method uses descriptive quantitative through environmental analysis. Lake Beratan water sampling was taken at 3 points, point 1 representing settlements and agriculture, point 2 representing the middle of the lake, and point 3 representing tourist areas. The data obtained was compared with the Class 1 Lake Water Quality Standards, Government Regulation Number 22 of 2021. The results showed that the BOD parameters still met the quality standards, so there were not too many organic pollutants in Lake Beratan. While the COD parameter exceeds the quality standard at all points. This shows that chemical pollutants originating from domestic activities around Lake Beratan such as agriculture using fertilizers and pesticides as well as tourism activities such as restaurants cause an increase in the COD value.